Identifying consumer behavior influence on fashion retailing in the COVID-19 pandemic situation - KARUNARATNE P.V.M; KARUNADASA M.P.V.D (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: The current research aims include analyzing the impact of COVID-19 on consumer behavior patterns in the fashion retail sector, determining how the level of buyer awareness influences consumer purchase behavior, and assessing the impact of online services on consumer behavior patterns in the fashion retail sector. There needs to be more research done on how fashion retail brands can best adjust to the new normal, as well as the demand for local brands, in the face of online marketing difficulties both during and after the lockdown. Methodology: The city of Kandy, located in Sri Lanka’s hill countryside, served as a focal fashion for the research because it is home to both fashion consumers and the 10 fashion brands examined in the study. Qualitative and quantitative techniques were used in this study’s data collection, organization, and analysis. Online shopping has been identified as a trend that has signaled a rapid increase due to changes in consumer behavior and the new trends of retailers. Research Results: A majority of shoppers (51.7%, to be exact) plan to keep making their purchases online going. A subset of consumers prefers traditional commerce, but they have been forced to adapt to new trade methods based on online purchasing, and this trend is expected to persist in the future. This study’s findings lend credence to the behavior that consumers’ responses to a pandemic will be complex and multifaceted. Retailers in the fashion industry will need to pay close attention to consumer preferences and adjust their stock and marketing strategies in light of the new restrictions on discretionary spending. Implications/Novel Contribution: Suggestions could be used to improve the fashion retail industry in Sri Lanka so that it can keep up with digital advancements in the future and endure when unforeseen events, such as a lockdown or global pandemic, strike the country.